Informed consent in cardiac surgery – current institutional practice and legislation - Karadžić Kočica, Milica; Ugrinović, Hristina; Grujić, Miloš; Lazović, Dejan; Vučićević, Filip; Panić, Goran; Kočica, Mladen (Vojnosanitetski pregled, 2022)
Background/Aim. Growing waiting lists for cardiac surgery have become a real problem in the Republic of Serbia, imposing serious difficulties in patient-surgeon communication. The aim of the study was to determine the current state of the institutional informed consent policy before elective cardiac surgical procedures in light of actual national legislation. Methods. An anonymous, voluntary survey was conducted among 200 consecutive patients at the Clinic for Cardiac Surgery, University Clinical Centre of Serbia, from September to December 2019, after signing an official institutional consent form. A targeted questionnaire was created to determine the quantity and quality of patients’ information about general and the most important aspects of cardiac surgical care. Results. The mean age of respondents was 66.2 years, with male predominance (68.0%), homogenous ethnicity, and low-to-middle (84.0%) education levels. A significant percentage had no information on the type of surgery (16.0%), extracorporeal circulation (46.0%), anaesthesia (56.0%) and transfusion (51.5%). Of those having some information, 7.0–20.0% graded them sufficient. The worst situation was recorded concerning risks of disease and surgical treatment, where 88.0% of patients had no information and almost 90.0% had some information and graded them as non-sufficient. Surprisingly, 81.5% of patients signed the consent form without any prior discussion with the operating surgeon. For 56.0% of patients, the information in the actual consent form was clear and sufficient. While 85.5% of patients claimed the importance, the others (14.5%) were not interested to know the most relevant information about their disease and surgery. Conclusion. The results unambiguously indicate an unacceptably low level of our patients’ information about the cardiac surgical procedure, extracorporeal circulation, anesthesia, transfusion, and estimated risk. The majority of them (85.5%) comprehends the importance and expects timely and adequate information. An extremely high percentage (81.5%) of patients had no chance to discuss the procedure with the operating surgeon. Both surgical indifference and insufficient knowledge of professional, ethical, and legal importance are the most important reasons for the actual informed consent policy in cardiac surgery.